2020
DOI: 10.1101/2020.12.23.424172
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pulmonary stromal expansion and intra-alveolar coagulation are primary causes of Covid-19 death

Abstract: SummaryMost Covid-19 victims are old and die from unrelated causes. Here we present twelve complete autopsies, including two rapid autopsies of young patients where the cause of death was Covid-19 ARDS. The main virus induced pathology was in the lung parenchyma and not in the airways. Most coagulation events occurred in the intra-alveolar and not in the intra-vascular space and the few thrombi were mainly composed of aggregated thrombocytes. The dominant inflammatory response was the massive accumulation of C… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 40 publications
0
9
0
5
Order By: Relevance
“…SEM for SARS-CoV-2 infected cells were performed as described previously (Szekely et al, 2020). Briefly, Cells grown on poly-L-lysin coated glass coverslips (Corning, United States) and 48h following infection the coverslips were fixed by immersion in 2.5% glutaraldehyde in 0.1M phosphate buffer, pH 7.4.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…SEM for SARS-CoV-2 infected cells were performed as described previously (Szekely et al, 2020). Briefly, Cells grown on poly-L-lysin coated glass coverslips (Corning, United States) and 48h following infection the coverslips were fixed by immersion in 2.5% glutaraldehyde in 0.1M phosphate buffer, pH 7.4.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…The suggestion in exploratory secondary analyses that there may be reduced need for extended oxygen supplementation in those treated with C21 hints that treatment with C21 may improve gas exchange at the alveolar level. This is interesting because AT2 progenitor cells, apparently the only cells in the lungs that express the AT2R, are the primary site for viral replication in the distal airways, prompting the hypothesis that C21 could restore lung function by a direct action on these cells [19 , 20] .…”
Section: Discussionmentioning
confidence: 99%
“…However, it has recently been described that the AT2R is highly expressed in alveolar type 2 (AT2) progenitor cells in the adult human lung and can be upregulated during repair and regeneration [14 , 19] . Moreover, the AT2 cells are the primary site of SARS-CoV-2 replication in the distal airways which is likely to contribute to the alveolar dysfunction and impaired gas exchange caused by the virus [20] .…”
Section: Introductionmentioning
confidence: 99%
“…The reduced need for extended oxygen supplementation indicates that treatment with C21 improves gas exchange at the alveolar level. The AT2 progenitor cells, apparently the only cells in the lungs that express the AT2R (18), are the primary site for viral replication in the distal airways (20), and it is suggested that C21 restores lung function by acting directly on these cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has recently been described that the AT2R is highly expressed in alveolar type 2 (AT2) progenitor cells in the adult human lung (18) and can be upregulated during repair and regeneration (19). Moreover, the AT2 cells are the primary site of SARS-CoV-2 replication in the distal airways (20) which is likely to contribute to the alveolar dysfunction and impaired gas exchange caused by the virus.…”
Section: Introductionmentioning
confidence: 99%